1992
DOI: 10.1212/wnl.42.12.2267
|View full text |Cite
|
Sign up to set email alerts
|

Cerebellar diaschisis revisited

Abstract: A unilateral supratentorial lesion may cause hypometabolism in the contralateral cerebellar hemisphere (crossed cerebellar diaschisis). We analyzed glucose metabolism, measured by PET-FDG, in the posterior fossa in 67 patients (78 PET studies) with primary unilateral supratentorial brain tumors selected for visually obvious metabolic asymmetry in the cerebellar hemispheres. We found that glucose utilization was 17% lower in the contralateral cerebellar cortex (compared with the ipsilateral one), consistent wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(16 citation statements)
references
References 0 publications
1
15
0
Order By: Relevance
“…Most cerebellar projections exit the cerebellum via the dentate nuclei (Dum and Strick, 2003) output to the thalamus and project to other cortical regions (Amino et al, 2001;Glickstein, 2007;Middleton and Strick, 1998;Zemanick et al, 1991). Functional connectivity studies demonstrated that apart from the thalamus, the cerebellum is also reciprocally connected to other structures via neural pathways such as the CSTC and cortico-ponto-cerebellar loops for higher cognitive functions (Desmond, 2001;Fulham et al, 1992;Ito, 2008;Middleton and Strick, 2000a,b;Schmahmann and Pandya, 1989). A sensorimotoranterior and cognitive-posterior functional localization dichotomy of the cerebellum has been proposed and supported by topological and meta-analytic studies Schmahmann, 1991Schmahmann, , 1996Schmahmann, , 2004Stoodley and Schmahmann, 2009).…”
Section: The Cerebellummentioning
confidence: 99%
“…Most cerebellar projections exit the cerebellum via the dentate nuclei (Dum and Strick, 2003) output to the thalamus and project to other cortical regions (Amino et al, 2001;Glickstein, 2007;Middleton and Strick, 1998;Zemanick et al, 1991). Functional connectivity studies demonstrated that apart from the thalamus, the cerebellum is also reciprocally connected to other structures via neural pathways such as the CSTC and cortico-ponto-cerebellar loops for higher cognitive functions (Desmond, 2001;Fulham et al, 1992;Ito, 2008;Middleton and Strick, 2000a,b;Schmahmann and Pandya, 1989). A sensorimotoranterior and cognitive-posterior functional localization dichotomy of the cerebellum has been proposed and supported by topological and meta-analytic studies Schmahmann, 1991Schmahmann, , 1996Schmahmann, , 2004Stoodley and Schmahmann, 2009).…”
Section: The Cerebellummentioning
confidence: 99%
“…The observed pattern of regional hypometabolism correlates with the anatomy of the CPC pathway [5], which transmits information about planned movement to the cerebellum [4]. Its corticopontine portion is uncrossed and builds synapses on the pontine nuclei.…”
mentioning
confidence: 77%
“…Second order neurons then cross to the opposite cerebellar cortex via the middle cerebellar peduncle. Disruption of the CPC pathway will cause hypometabolism on the PET scan in the ipsilateral pons and the contralateral cerebellar cortex [5,6], resulting in crossed cerebellar diaschisis (reduced blood flow or metabolism in the cerebellum contralateral to a cerebral insult [7,8]). Disruption of the CPC tract may have contributed to cerebellar-like ataxia in our patient.…”
mentioning
confidence: 99%
“…This phenomenon of diaschisis was initially described by von Monakow [14] as focal cerebral lesions that cause temporary impairment of function at a remote site and in children in a 123 I-amphetamine SPECT study [15]. Until now, the exact pathophysiologic mechanism of this phenomenon has remained unclear [16]. The presently described delayed onset and the subacute development of symptoms of AIS after posterior fossa surgery resembles the clinical course at onset of PFS.…”
Section: Discussionmentioning
confidence: 98%